Cambodia : Rural Sector Strategy Note, Towards a Strategy for Rural Growth and Poverty Reduction - World Bank (Washington, DC, 2012)
Recovering from three decades of conflict, over this last decade, Cambodia has undergone dramatic economic, political, and social transitions. Cambodia experienced rapid institutional changes as it restored peace, moved from a centrally planned to a market-oriented economy, and moved from isolation to regional and global integration. Cambodia has achieved political and macroeconomic stability, and has initiated key structural reforms. Nevertheless, Cambodia's economy remains vulnerable, and economic growth has not translated into widespread poverty reduction. With a GDP per capita of US$280, and social indicators showing little progress since the 1960s, Cambodia remains one of the poorest countries in the world. The legacies of war - the losses in physical and social capital, depleted human capital, and the remaining land mines - will continue to challenge the country's overall development in the short, and medium terms. In addition, the country's small and open economy is faced with the challenge of establishing institutions and infrastructure that will allow it to realize the benefits, and mitigate the risks of regional and global integration, in an increasingly competitive regional environment. To a great extent, progress will depend on achievements in rural areas. The purpose of this Note is to provide a broad framework to explore options for Cambodia's future directions for rural development with the government, donors and other development partners. The Note provides a profile of existing conditions in the rural sector, and highlights areas for priority attention to achieve broad-based and healthy growth rates, sufficient to enable the rural sector to continue contributing significantly to rural and non-rural incomes and employment. The note is organized in three main parts. Part I provides an overview of the performance of Cambodia's rural economy. Part II reviews the key issues affecting the rural sector, and proposes elements of a pro-poor agriculture and rural development strategy. Part III discusses cross-cutting issues affecting the delivery of results, as well as proposals for follow-on activities to this Note.